Policy Leadership in Terms of Crisis Management in Higher Education - Runcheva Tasev, Hristina (University Goce Delchev Shtip, 2016)
Experience confirms that the actual planning includes the coordination of institutions, education, assessments and psychology. Anyone who can foresee the consequences of each procedure can act responsibly in taking steps to address the challenges of the complexity of the modern era.Education is one of the key pillars in raising new generations,prepared to manage contemporary social trends. The paper aims to present a ctitical apporach of how education is necessary for leadership in terms of crisis management, particularly in higher education. The paper responds to what profile of leaders a country needs to be able to address the challenges; how to prepare potential young leaders for crisis management, how be prepared before the emergency and how to get out of unexpected circumstances. In addition, the paper will give an overview of that how education can affect leadership in the process of policy making and in terms of preparedness for crisis management (early and efficient collection of information, early warning mechanisms, cooperation with different actors, priorities in action, etc.). Rapid and effective decision-making and political communication are also part of the pillars of successful leadership in times of crisis management, which require appropriate education.
Keywords: Education, crisis management, policy making, leadership.